Vitamin D and High Blood Pressure - Prado da Silva, Karine Cristine; Feracin da Silva Picoli, Maria Eleonora; de Oliveira Rossignolo, Simone Camargo; Pietro, Luciana (Clinical Medicine And Health Research Journal, 2023)
Introduction: Cardiovascular diseases are the main cause of death in the world, and some of these diseases can be controlled or avoided with a healthier lifestyle. These diseases are often associated with the emergence of other diseases such as diabetes mellitus, obesity, high cholesterol levels and high blood pressure. Research has shown that vitamin D deficiency can be a factor that also helps in the appearance of these diseases, since if the serum levels of vitamin D are adequate, it can help in the control and prevention of these diseases. Objectives: To evaluate the relationship between vitamin D and cardiovascular diseases, specifically systemic arterial hypertension and its effects. Methods: A systematic review was carried out by searching for original articles in scientific databases: Pubmed, Science Direct, Lilacs and Scielo in English and Portuguese. Results: No conclusive data were found for the indication of vitamin D supplementation in the treatment of systemic arterial hypertension, due to its lack of efficiency so far, requiring further research to better clarify the subject. Conclusion: The results obtained do not present conclusive data for the indication of vitamin D supplementation in the treatment of systemic arterial hypertension, due to its lack of efficiency up to the present moment, more research is necessary for a better clarification on the subject.